2008
DOI: 10.1167/iovs.07-0493
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Matrix 24-2 and Original N-30 Frequency-Doubling Technology Tests Compared with Standard Automated Perimetry

Abstract: The performance of the Matrix FDT 24-2 was similar to that of the first-generation FDT N-30. The Matrix FDT 24-2 test was consistently better than SAP at discriminating between healthy and glaucomatous eyes. Further studies are needed to evaluate the ability of the Matrix FDT 24-2 to monitor glaucoma progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 27 publications
1
36
1
1
Order By: Relevance
“…Future studies should include results of the FDT Matrix, which has a higher spatial resolution. 43 Our results indicate that additional determination of morphometric integrity in this case RNFL thickness assessed by SDOCT can be justified especially in early diagnosis; in preperimetric patients the sensitivity of SDOCT is considerable higher than sensitivity of the presently used FDT perimeter. In more advanced stages of glaucoma the diagnostic value of both devices seem to be comparable.…”
Section: Discussionmentioning
confidence: 67%
“…Future studies should include results of the FDT Matrix, which has a higher spatial resolution. 43 Our results indicate that additional determination of morphometric integrity in this case RNFL thickness assessed by SDOCT can be justified especially in early diagnosis; in preperimetric patients the sensitivity of SDOCT is considerable higher than sensitivity of the presently used FDT perimeter. In more advanced stages of glaucoma the diagnostic value of both devices seem to be comparable.…”
Section: Discussionmentioning
confidence: 67%
“…We found higher mean values in the eye with Akreos AO in all areas (A1 to A4), but a statistical difference (P=0.043) was found only in the 20 o field area (A3). Although the chan ges were not statistically significant, it is noteworthy that an improvement in the perimetry values with such lenses could mask the diagnosis of glaucoma or lead to other diagnostic confusions, especially considering that the functional abnormalities detected by FDT perimetry were shown to be predictive of the future onset and location of VF loss among suspected glaucoma patients (13)(14)(15) . The results of the present study indicate that MD values were higher in the Akreos AO group, and the PSD was higher in the Akreos Fit group.…”
Section: Discussionmentioning
confidence: 87%
“…Maddess et al (12) proposed that a CS test based on the frequency-doubling illusion should be effective in the detection of early glaucomatous VF loss. However, previous studies have yielded divergent views regarding the diagnostic performance of FDT perimetry to standard automatic white-on-white perimetry (SAP) for the detection of glaucoma (13)(14)(15) . Because previous studies have demonstrated an improvement in CS in eyes implanted with aspheric IOLs (6)(7)(8)(9)(10) , is important to investigate its influence on the results of FDT.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to SAP, FDT Matrix also provides raw sensitivity values, total and pattern deviation probability plots, and the summary indices of MD and PSD. Matrix FDT has been reported by some to be better than SAP for discriminating glaucomatous and healthy eyes (Racette et al, 2008); however, others found no difference between Matrix FDT and SAP (Spry et al, 2005). SWAP has also been modified over the years and now utilizes the SITA strategy to shorten the test duration.…”
Section: Figurementioning
confidence: 99%